Anode for lithium secondary battery, lithium secondary battery, method for manufacturing anode for lithium secondary battery, and method for manufacturing lithium secondary battery
The use of a phosphorus and oxygen-containing coat layer on lithium secondary battery electrodes, combined with additional materials, addresses the issue of dendrite-induced short circuits, improving cycle life and energy density for various power sources.
Patent Information
- Application Number
- JP2020193872
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-11-20
AI Technical Summary
Lithium secondary batteries using lithium metal as the negative electrode active material are prone to short circuits due to the growth of dendritic lithium, which can penetrate the separator and cause a short circuit.
A negative electrode with a first coat layer containing phosphorus, fluorine, and oxygen atoms, and optionally a second coat layer with materials like gold, tin, or carbon nanotubes, is applied to the surface of the negative electrode base material to suppress dendrite growth and maintain a stable film, reducing current concentration and preventing short circuits.
The proposed electrode structure effectively suppresses short circuits, enhances charge/discharge cycle life, and maintains high energy density, making it suitable for applications in automobiles, flying vehicles, personal computers, and electronic devices.
Smart Images

Figure 0007600636000003 
Figure 0007600636000004 
Figure 0007600636000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a lithium secondary battery, a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a method for producing a lithium secondary battery. [Background technology]
[0002] Due to their high energy density, lithium ion secondary batteries are widely used in personal computers, flying objects such as airplanes, electronic devices such as communication terminals, automobiles, etc. The lithium ion secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to be charged and discharged by transferring electricity between the electrodes.
[0003] In recent years, in order to increase the capacity of lithium ion secondary batteries, there has been a demand for high-capacity negative electrodes. Lithium metal has a significantly higher discharge capacity per active material mass than graphite, which is currently widely used as a negative electrode active material for lithium ion secondary batteries. That is, while the theoretical capacity per mass of graphite is 372 mAh / g, the theoretical capacity per mass of lithium metal is 3860 mAh / g, which is significantly larger. For this reason, lithium secondary batteries using lithium metal as the negative electrode active material have been proposed (see JP 2011-124154 A). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-124154 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in lithium secondary batteries that use lithium metal as the negative electrode active material, lithium metal may deposit in a dendritic form on the surface of the negative electrode during charging (hereinafter, lithium metal in a dendritic form is referred to as a "dendrite.") When this dendrite grows, it may penetrate the separator and come into contact with the positive electrode, causing a short circuit.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a negative electrode for a lithium secondary battery that can suppress the occurrence of a short circuit in the lithium secondary battery. [Means for solving the problem]
[0007] One aspect of the present invention is a negative electrode comprising a negative electrode base material layer and a first coating layer laminated directly or indirectly on a surface of the negative electrode base material layer, the first coating layer containing a phosphorus compound containing fluorine atoms and oxygen atoms, and a spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy shows that 2P The negative electrode for a lithium secondary battery has a peak position of 135 eV or higher.
[0008] Another aspect of the present invention is a method for producing a negative electrode comprising the steps of: laminating a first coating layer directly or indirectly on a surface of a negative electrode substrate layer by applying a first coating layer forming material containing a phosphorus compound containing fluorine atoms and oxygen atoms; and determining whether the first coating layer has a P 2P The present invention relates to a method for producing a negative electrode for a lithium secondary battery, in which the peak position of Effect of the Invention
[0009] According to the negative electrode for a lithium secondary battery according to one aspect of the present invention, the occurrence of a short circuit in the lithium secondary battery can be suppressed. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is an external perspective view showing a lithium secondary battery according to one embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic diagram showing an electricity storage device formed by assembling a plurality of lithium secondary batteries according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] First, an outline of the negative electrode of a lithium secondary battery, the lithium secondary battery, the method for manufacturing the negative electrode of a lithium secondary battery, and the method for manufacturing a lithium secondary battery disclosed in this specification will be described.
[0012] One aspect of the present invention is a negative electrode comprising a negative electrode base material layer and a first coating layer laminated directly or indirectly on a surface of the negative electrode base material layer, the first coating layer containing a phosphorus compound containing fluorine atoms and oxygen atoms, and a spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy shows that 2P The negative electrode for a lithium secondary battery has a peak position of 135 eV or higher.
[0013] According to the negative electrode for lithium secondary batteries, the occurrence of short circuits in lithium secondary batteries can be suppressed. The reason is unclear, but the following reason is presumed. In general, when a non-aqueous electrolyte is used as a non-aqueous electrolyte in a lithium secondary battery, the degree of freedom of the deposition site of lithium metal is high, and current is likely to concentrate on the site where lithium metal is likely to deposit in response to the non-uniformity of the deposition site. This promotes the growth of dendrites on the surface of the negative electrode during charging, which may cause a short circuit early. In addition, the dendrites are likely to be electrically isolated by dissolving the lithium metal on the surface of the negative electrode during subsequent discharge. In contrast, the negative electrode for lithium secondary batteries has a first coating layer containing a phosphorus compound containing fluorine atoms and oxygen atoms directly or indirectly on the surface of the negative electrode base material layer, and in a spectrum by X-ray photoelectron spectroscopy of the surface of the first coating layer, P 2Pis 135 eV or more, the first coating layer acts as a supply source of the phosphorus compound, and when the coating on the negative electrode surface is consumed with charge / discharge cycles, a necessary amount of the phosphorus compound dissolves from the first coating layer to form a coating, and a good coating is always maintained on the negative electrode surface. As a result, it is considered that the growth of dendrites is suppressed and the occurrence of short circuits is delayed. In addition, by forming the first coating layer directly or indirectly on the surface of the negative electrode base material layer in advance, the growth of dendrites toward the positive electrode due to the precipitation of lithium metal is physically suppressed. As a result, it is considered that the growth of dendrites is suppressed and the occurrence of short circuits is delayed. Therefore, the negative electrode for lithium secondary batteries can suppress the occurrence of short circuits in lithium secondary batteries.
[0014] In the present invention, the term "lithium secondary battery" refers to a secondary battery in which lithium ions are exchanged between a positive electrode and a negative electrode via a non-aqueous electrolyte, and which uses lithium metal as the negative electrode active material. Note that the "lithium secondary battery" of the present disclosure also includes a lithium-air battery.
[0015] In the negative electrode for lithium secondary batteries, a second coating layer is provided between the negative electrode substrate layer and the first coating layer, and is laminated directly or indirectly on the surface of the negative electrode substrate layer, and the second coating layer is preferably composed mainly of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes. The negative electrode for lithium secondary batteries further comprises a second coating layer between the negative electrode substrate layer and the first coating layer, and on the surface of the negative electrode substrate layer, the second coating layer being composed mainly of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes, so that the occurrence of a short circuit in the lithium secondary battery can be further suppressed. The reason for this is unclear, but the following reason is presumed. As described above, the negative electrode for lithium secondary batteries has a first coating layer containing a phosphorus compound containing fluorine atoms and oxygen atoms directly or indirectly on the surface of the negative electrode substrate layer, so that a good coating is always maintained on the negative electrode surface, and current concentration due to non-uniformity of the coating resistance is reduced. Furthermore, by coating the negative electrode substrate layer and the first coating layer and the surface of the negative electrode substrate layer directly or indirectly with a second coating layer mainly composed of at least one of the gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes, the components of the second coating layer act as a deposition site for lithium metal, thereby further reducing current concentration. In addition, since the negative electrode for the lithium secondary battery maintains a stable coating due to the first coating layer, it is considered that the lithium metal is less likely to be isolated and the role of the above-mentioned components as a deposition site is sustained for a long period of time. Therefore, it is presumed that the negative electrode for the lithium secondary battery is provided with a combination of the first coating layer and the second coating layer to further suppress the occurrence of short circuits. Here, the term "main component" refers to the component with the highest content, that is, the component contained in the total mass of 50% by mass or more.
[0016] The negative electrode preferably includes a lithium metal layer laminated between the negative electrode substrate layer and the first coating layer, which functions as a negative electrode active material layer and also functions as a lithium supply layer that compensates for the amount of electricity that is no longer able to contribute to charging and discharging due to electrical isolation of dendrites.
[0017] The negative electrode preferably includes a lithium metal layer laminated between the negative electrode base layer and the second coating layer, between the first coating layer and the second coating layer, or a combination thereof. By including the lithium metal layer in the negative electrode, the amount of electricity corresponding to lithium that cannot contribute to charging and discharging due to electrical isolation of dendrites can be compensated for by the lithium metal layer.
[0018] The lithium secondary battery includes the negative electrode. Since the lithium secondary battery includes the negative electrode, the occurrence of a short circuit is suppressed. The lithium secondary battery has a high improvement effect on the reduction in charge-discharge cycle life due to the occurrence of a short circuit, which has been a conventional problem. Therefore, the lithium secondary battery is suitable for various power sources, such as power sources for automobiles such as electric vehicles (EVs), hybrid vehicles (HEVs), and plug-in hybrid vehicles (PHEVs), power sources for aircraft such as airplanes and drones, power sources for electronic devices such as personal computers and communication terminals, and power storage power sources. Among them, the lithium secondary battery is particularly suitable as a power source for aircraft because it combines an extremely high mass energy density, which is particularly required for a power source for an aircraft, with sufficient charge-discharge cycle performance.
[0019] Another aspect of the present invention is a method for producing a negative electrode comprising the steps of: laminating a first coating layer directly or indirectly on a surface of a negative electrode substrate layer by applying a first coating layer forming material containing a phosphorus compound containing fluorine atoms and oxygen atoms; and determining whether the first coating layer has a P 2PThe method for producing a negative electrode for a lithium secondary battery includes coating a surface of a negative electrode substrate layer with a first coating layer-forming material containing a phosphorus compound containing fluorine atoms and oxygen atoms, thereby laminating a first coating layer directly or indirectly on the surface of the negative electrode substrate layer, and determining in a spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy that the peak position of 2P It is considered that, since the peak position of is 135 eV or more, a good coating is always maintained on the surface of the negative electrode, and as a result, the growth of dendrites is suppressed and the occurrence of a short circuit is delayed. Therefore, the method for producing a negative electrode for a lithium secondary battery can produce a negative electrode for a lithium secondary battery that can suppress the occurrence of a short circuit in the lithium secondary battery.
[0020] The method for producing a lithium secondary battery includes producing a lithium secondary battery using the negative electrode or a negative electrode obtained by the method for producing a negative electrode. Since the method for producing a lithium secondary battery includes producing a lithium secondary battery using the negative electrode or a negative electrode obtained by the method for producing a negative electrode, a lithium secondary battery in which the occurrence of short circuits is suppressed can be produced.
[0021] The configuration of the negative electrode for a lithium secondary battery according to one embodiment of the present invention, the configuration of the lithium secondary battery, and a method for manufacturing the negative electrode for a lithium secondary battery, a method for manufacturing a lithium secondary battery, and other embodiments will be described in detail below. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.
[0022] <Anode for lithium secondary batteries> A negative electrode for a lithium secondary battery according to one embodiment of the present invention comprises a negative electrode substrate layer and a first coating layer laminated directly or indirectly on a surface of the negative electrode substrate layer.
[0023] (Negative electrode base material layer) The negative electrode substrate layer has electrical conductivity. Whether or not it has "electrical conductivity" is determined by a volume resistivity of 10 or less as measured in accordance with JIS-H-0505 (1975).7 The threshold value is Ω·cm. The material of the negative electrode substrate layer may be a metal such as copper, nickel, stainless steel, or nickel-plated steel, or an alloy of these metals, or a carbonaceous material. Among these, copper or a copper alloy is preferred. The negative electrode substrate layer may be a foil, a vapor deposition film, a mesh, a porous material, or the like, and from the viewpoint of cost, a foil is preferred. Therefore, the negative electrode substrate layer is preferably a copper foil or a copper alloy foil. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0024] The average thickness of the negative electrode substrate layer is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, even more preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate layer within the above range, it is possible to increase the strength of the negative electrode substrate layer and to increase the energy density per volume of the lithium secondary battery.
[0025] (First coating layer) The first coating layer is laminated directly or indirectly on the surface of the negative electrode substrate layer, and contains a phosphorus compound containing fluorine atoms and oxygen atoms.
[0026] Examples of the phosphorus compound containing a fluorine atom and an oxygen atom include lithium difluorophosphate (LiDFP), lithium tetrafluorooxalate phosphate, lithium difluorobisoxalate phosphate, and lithium (fluorosulfonyl)(difluorophosphoryl)imide.
[0027] P in the spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy 2P The lower limit of the peak position of is 135 eV, and preferably 136 eV. 2P The upper limit of the peak position of is preferably 138 eV, more preferably 137 eV. 2PWhen the peak position of is within the above range, the first coating layer acts as a supply source of the phosphorus compound, and when the coating on the negative electrode surface is consumed with charge / discharge cycles, a necessary amount of the phosphorus compound dissolves from the first coating layer to form a coating, and a good coating is always maintained on the negative electrode surface. As a result, it is considered that the growth of dendrites is suppressed and the occurrence of short circuits is delayed. 2P The peak position is a value obtained by measuring the surface of the first coating layer in a lithium secondary battery in a fully discharged state.
[0028] The sample used for the measurement of the spectrum of the first coating layer surface of the negative electrode by X-ray photoelectron spectroscopy (XPS) is prepared by the following method. The lithium secondary battery is discharged at a current of 0.1 C to the discharge end voltage during normal use to make it in a fully discharged state. Here, "normal use" refers to the case where the lithium secondary battery is used under the discharge conditions recommended or specified for the lithium secondary battery. The lithium secondary battery in the fully discharged state is disassembled to remove the negative electrode, which is thoroughly washed using dimethyl carbonate, and then dried under reduced pressure at room temperature. The dried negative electrode is cut to a predetermined size (e.g., 2 cm x 2 cm) to be used as a sample for the measurement of the spectrum by XPS. The work from disassembling the lithium secondary battery to the measurement of the spectrum by XPS is performed in an argon atmosphere with a dew point of -60°C or less. The equipment and measurement conditions used for the measurement of the spectrum by XPS of the first coating layer surface of the negative electrode are as follows. Equipment: KRATOS ANALYTICAL's "AXIS NOVA" X-ray source: monochromatic AlKα Tube voltage: 15kV Tube current: 10mA Neutralization gun: ON Analysis area: 700μm x 300μm Measurement range: P 2P =150~120eV, C 1S =300~270eV Measurement interval: 0.1 eV Dwell Time: 2P = 426 ms, C1S = 250 milliseconds Accumulation count: P 2P =20 times, C 1S = 10 times
[0029] In addition, P in the above spectrum 2P The peak positions are determined using CasaXPS (Casa Software) as follows. First, the binding energy of the sp2 carbon peak in C1s is set to 284.8 eV, and all the spectra obtained are corrected. Next, the background is removed from each spectrum using the Shirley method. The binding energy at which the peak intensity of the peak in the range of 130 to 138 eV in the spectrum obtained in this way is the highest is defined as P 2P The peak position is
[0030] (Second coating layer) The negative electrode for lithium secondary batteries is preferably provided with a second coating layer between the negative electrode substrate layer and the first coating layer and laminated directly or indirectly on the surface of the negative electrode substrate layer. The second coating layer is preferably mainly composed of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes. The negative electrode for lithium secondary batteries is further provided with a second coating layer mainly composed of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes on the surface of the negative electrode substrate layer, and the components of the second coating layer act as precipitation sites for lithium metal, thereby further reducing current concentration. Therefore, the occurrence of a short circuit in the lithium secondary battery can be further suppressed. As the main component of the second coating layer, gold, tin, aluminum, carbon nanotubes, or a combination thereof is more preferable from the viewpoint of further suppressing the occurrence of a short circuit in the lithium secondary battery.
[0031] The lower limit of the content of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these, and carbon nanotubes in the second coating layer is preferably 50 mass %, more preferably 90 mass %. By setting the content of the above components in the second coating layer within the above range, the occurrence of a short circuit in the lithium secondary battery can be further suppressed.
[0032] The lower limit of the average thickness of the second coating layer is preferably 1 nm, more preferably 15 nm. On the other hand, the upper limit of the average thickness of the second coating layer is preferably 1000 nm, more preferably 800 nm, and even more preferably 500 nm. By setting the average thickness of the second coating layer within the above range, the above components act appropriately as precipitation sites for lithium metal, so that the occurrence of a short circuit can be further suppressed. The "average thickness of the coating layer" refers to the value obtained by dividing the mass of the coating layer on the negative electrode by the area of the coating layer on the negative electrode, and then dividing the result by the true density of the coating layer.
[0033] The lower limit of the coating amount of the second coating layer is 0.0019 mg / cm 2 is preferred, and 0.029 mg / cm 2 On the other hand, the upper limit of the coating amount of the second coating layer is 1.90 mg / cm. 2 is preferred, and 1.50 mg / cm 2 More preferably, 0.97 mg / cm 2 By setting the coating amount of the second coating layer within the above range, the above components appropriately act as precipitation sites for lithium metal, so that the occurrence of short circuits can be further suppressed.
[0034] (Lithium metal layer) The negative electrode preferably includes a lithium metal layer. The lithium metal layer functions as a negative electrode active material layer or a lithium supplement layer. Therefore, the lithium metal layer supplies the negative electrode active material and can supplement the amount of electricity equivalent to lithium that cannot contribute to charging and discharging due to electrical isolation of dendrites.
[0035] The lithium metal layer contains lithium metal as the negative electrode active material. By containing lithium metal as the negative electrode active material, the discharge capacity per active material mass can be improved. The lithium metal includes lithium alloys in addition to simple lithium. Examples of the lithium alloy include lithium aluminum alloys, lithium silver alloys, lithium zinc alloys, lithium calcium alloys, lithium magnesium alloys, and lithium indium alloys. The lithium alloy may contain a plurality of metal elements other than lithium. Examples of the lithium metal layer include a lithium metal thin film and lithium metal particles. The negative electrode containing lithium metal can be manufactured by cutting or forming lithium metal into a predetermined shape.
[0036] When the negative electrode does not include the second coating layer, the lithium metal layer is provided between the negative electrode base material layer and the first coating layer, and when the negative electrode includes the second coating layer, it is preferred that the lithium metal layer is provided between the negative electrode base material layer and the second coating layer.
[0037] When the lithium secondary battery includes a positive electrode active material containing lithium, the negative electrode may not initially include a lithium metal layer, and lithium metal may be deposited on the surface of the negative electrode substrate layer during charging, and the lithium metal deposited on the surface of the negative electrode substrate layer may dissolve during discharging. That is, during charging, a negative electrode including the negative electrode substrate layer and lithium metal may be the negative electrode, and during discharging, the negative electrode substrate layer may be the negative electrode. In this case, lithium ions are initially supplied from the positive electrode active material containing lithium by initial charging, and as a result, a lithium metal layer is formed between the negative electrode substrate layer and the first coat layer or between the first coat layer and the second coat layer in the negative electrode. In this case, when the negative electrode does not include the second coat layer, it is preferable that the lithium metal layer is laminated between the negative electrode substrate layer and the first coat layer, and when the negative electrode includes the second coat layer, it is preferable that the lithium metal layer is laminated between the first coat layer and the second coat layer.
[0038] When a metal foil (eg, copper foil) is used as the negative electrode substrate layer, an alloy layer containing lithium and a metal (eg, copper) that is a component of the metal foil may be formed between the metal foil and the lithium metal layer.
[0039] The negative electrode for the lithium secondary battery may include an intermediate layer disposed between the negative electrode substrate layer and the lithium metal layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the negative electrode substrate layer and the lithium metal layer. The configuration of the intermediate layer is not particularly limited, and may include, for example, a binder and a conductive agent.
[0040] According to the negative electrode for a lithium secondary battery according to one embodiment of the present invention, the occurrence of a short circuit in the lithium secondary battery can be suppressed.
[0041] <Lithium secondary battery> A lithium secondary battery according to one embodiment of the present invention includes an electrode assembly having a negative electrode, a positive electrode, and a separator for the lithium secondary battery described above, a non-aqueous electrolyte, and a container for accommodating the electrode assembly and the non-aqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with separators interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The non-aqueous electrolyte is present in a state in which it is contained in the positive electrode, the negative electrode, and the separator.
[0042] [Negative electrode] The lithium secondary battery includes a negative electrode for the lithium secondary battery. Since the lithium secondary battery includes a negative electrode for the lithium secondary battery, the occurrence of a short circuit is suppressed. In addition, since the first coating layer containing a phosphorus compound containing fluorine atoms and oxygen atoms is provided directly or indirectly on the surface of the negative electrode base material layer, selective consumption of the phosphorus compound on the negative electrode surface side is promoted and the growth of the coating formed on the positive electrode surface side is suppressed, so that it is presumed that there is also an effect of suppressing an increase in resistance on the positive electrode side. The specific configuration of the negative electrode for the lithium secondary battery is as described above.
[0043] [Positive electrode] The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the negative electrode above.
[0044] The positive electrode substrate has electrical conductivity. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high electrical conductivity, and cost. Examples of the positive electrode substrate include foil, vapor deposition film, mesh, and porous material, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H4160 (2006).
[0045] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the lithium secondary battery.
[0046] The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.
[0047] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for lithium secondary batteries. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni(1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.
[0048] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0049] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.
[0050] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.
[0051] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.
[0052] The content of the conductive agent in the positive electrode active material layer is preferably 1% by mass to 10% by mass, more preferably 3% by mass to 9% by mass. By setting the content of the conductive agent in the above range, the energy density of the lithium secondary battery can be increased.
[0053] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0054] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the active material can be stably held.
[0055] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.
[0056] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.
[0057] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.
[0058] [Separator] The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the form of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these forms, a porous resin film is preferable from the viewpoint of strength, and a nonwoven fabric is preferable from the viewpoint of the liquid retention of the non-aqueous electrolyte. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the negative electrode substrate layer of the separator.
[0059] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, barium titanate, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride and barium fluoride; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of lithium secondary batteries.
[0060] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.
[0061] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.
[0062] [Non-aqueous electrolyte] The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0063] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.
[0064] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, FEC is preferred.
[0065] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate (TFEMC), bis(trifluoroethyl) carbonate, etc. Among these, DMC and TFEMC are preferred.
[0066] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.
[0067] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.
[0068] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.
[0069] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.
[0070] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include halogenated carbonates such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC); oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexyl, and the like. Aromatic compounds such as benzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the above aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, Glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, propane sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2- dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like.These additives may be used alone or in combination of two or more.
[0071] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.
[0072] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.
[0073] The solid electrolyte can be selected from any material that has ion conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (for example, 15° C. to 25° C.) Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, oxynitride solid electrolytes, polymer solid electrolytes, etc.
[0074] As the sulfide solid electrolyte, in the case of a lithium secondary battery, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 , etc.
[0075] [Specific configuration of lithium secondary battery] The shape of the lithium secondary battery of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery.
[0076] Fig. 1 shows a lithium secondary battery 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.
[0077] [Configuration of the power storage device] The lithium secondary battery of this embodiment can be mounted as a power storage unit (battery module) comprising a plurality of lithium secondary batteries 1 assembled together, in a power source for automobiles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., a power source for flying objects such as airplanes and drones, a power source for electronic devices such as personal computers and communication terminals, a power source for power storage, etc. In this case, it is sufficient that the technology of the present invention is applied to at least one of the lithium secondary batteries included in the power storage unit.
[0078] 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected lithium secondary batteries 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects the two or more lithium secondary batteries 1, a bus bar (not shown) that electrically connects the two or more energy storage units 20, and the like. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more lithium secondary batteries.
[0079] <Method of manufacturing negative electrodes for lithium secondary batteries> The method for manufacturing a negative electrode for a lithium secondary battery includes laminating a first coating layer directly or indirectly on a surface of a negative electrode substrate layer by applying a first coating layer-forming material containing a phosphorus compound including fluorine atoms and oxygen atoms.
[0080] The first coating layer forming material can be prepared by dissolving or dispersing a phosphorus compound containing fluorine and oxygen atoms in a solvent. Examples of the phosphorus compound include lithium difluorophosphate (LiDFP), lithium tetrafluorooxalate phosphate, lithium difluorobisoxalate phosphate, and lithium (fluorosulfonyl) (difluorophosphoryl) imide. Examples of the solvent include 1,2-dimethoxyethane (DME).
[0081] In the step of laminating the first coating layer directly or indirectly on the surface of the substrate layer, first, droplets of the material for forming the first coating layer are dropped directly or indirectly on the surface of the negative electrode substrate layer so that the amount dropped per unit area is the same. Next, the first coating layer is laminated directly or indirectly on the surface of the negative electrode substrate layer by performing natural drying and vacuum drying. Examples of the coating method of the first coating layer include spraying with a spray, coating with a dip coater, coating with a spin coater, and coating with a roll coater.
[0082] In the spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy, P 2P The method for producing a negative electrode for a lithium secondary battery includes coating a surface of a negative electrode substrate layer with a first coating layer-forming material containing a phosphorus compound containing fluorine atoms and oxygen atoms, thereby laminating a first coating layer directly or indirectly on the surface of the negative electrode substrate layer, and determining in a spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy that the peak position of P 2P It is considered that, when the peak position of is 135 eV or more, a good coating is always maintained on the surface of the negative electrode, and as a result, the growth of dendrites is suppressed and the occurrence of a short circuit is delayed. Therefore, the method for producing a negative electrode for a lithium secondary battery can produce a negative electrode for a lithium secondary battery that can suppress the occurrence of a short circuit in the lithium secondary battery.
[0083] The method for producing a negative electrode for a lithium secondary battery preferably includes laminating a lithium metal layer between the negative electrode substrate layer and the first coating layer. The step of laminating the lithium metal layer can be performed, for example, by pressing the negative electrode substrate layer and the lithium metal layer together.
[0084] In the method for producing a negative electrode for a lithium secondary battery, it is preferable to directly or indirectly laminate a second coating layer on the surface of the negative electrode base material layer before laminating the first coating layer. Examples of the method for laminating the second coating layer include sputtering, vapor deposition, plating, coating, etc. of the material for the second coating layer.
[0085] <Method of manufacturing lithium secondary battery> The method for producing a lithium secondary battery according to one embodiment of the present invention includes producing a lithium secondary battery using the above-mentioned negative electrode or a negative electrode obtained by the method for producing the negative electrode. Since the method for producing a lithium secondary battery includes producing a lithium secondary battery using the negative electrode or a negative electrode obtained by the method for producing the negative electrode, a lithium secondary battery in which short circuit occurrence is suppressed can be produced. The method for producing a lithium secondary battery includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and housing the electrode body and the non-aqueous electrolyte in a container. Preparing the electrode body includes preparing a positive electrode, preparing the negative electrode, and forming an electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween. Preparing the negative electrode includes using the negative electrode or a negative electrode obtained by the method for producing the negative electrode.
[0086] The method of storing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution is injected from an injection port formed in the container, and then the injection port is sealed. The details of each element constituting the lithium secondary battery obtained by this manufacturing method are as described above.
[0087] [Other embodiments] The lithium secondary battery of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0089] [Examples 1, 2, and 4, and Comparative Example 1] (Preparation of negative electrode) A copper foil having an average thickness of 10 μm was prepared as the metal foil constituting the negative electrode base material layer. After laminating a lithium metal plate having a thickness of 100 μm on the copper foil, a first coating layer shown in Table 1 was laminated on the surface of the lithium metal plate. The first coating layer was formed according to the following procedure. Each of the negative electrodes thus obtained was rectangular with a width of 32 mm and a length of 42 mm.
[0090] (Formation of the first coating layer) Lithium difluorophosphate (LiDFP) was dissolved in 1,2-dimethoxyethane (DME) solvent to prepare a solution. The concentration of LiDFP in the solution was 5.0 mass %, and this was used as the first coating layer forming material. Next, the first coating layer forming material was dropped onto the surface of the lithium metal plate with a dropper so that the drop amount per unit area was the same, and the material was allowed to spread naturally, after which it was naturally dried and vacuum dried. The coating amount of the first coating layer was about 0.60 mg / cm. 2 It was.
[0091] (Preparation of positive electrode) The positive electrode active material has an α-NaFeO2 type crystal structure and Li 1+α Me 1-αA lithium transition metal composite oxide represented by O2 (Me is a transition metal) was used. Here, the molar ratio of Li to Me, Li / Me, was 1.33, and Me was composed of Ni and Mn, and was contained in a molar ratio of Ni:Mn=0.33:0.67.
[0092] Next, a positive electrode paste was prepared containing the positive electrode active material, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and phosphonic acid in a mass ratio of 92.25:4.5:3.0:0.25, using N-methylpyrrolidone (NMP) as a dispersion medium. The positive electrode paste was applied to one side of an aluminum foil having an average thickness of 15 μm as a positive electrode substrate, dried, and pressed to prepare a positive electrode having a positive electrode active material layer. The coating amount of the positive electrode active material layer was 26.5 mg / cm. 2 The porosity was 40%. The positive electrode thus fabricated was rectangular with a width of 30 mm and a length of 40 mm.
[0093] (Preparation of non-aqueous electrolyte) As the non-aqueous solvent, fluoroethylene carbonate (FEC) and 2,2,2-trifluoroethyl methyl carbonate (TFEMC) were used. LiPF6 was added at 1 mol / dm 3 to give a non-aqueous electrolyte.
[0094] (Production of lithium secondary batteries) A polypropylene microporous membrane was used as the separator. The positive electrode and the negative electrode were laminated with the separator interposed therebetween to prepare an electrode body. The electrode body was placed in a container, the non-aqueous electrolyte was injected therein, and the container was sealed by thermal welding to obtain the lithium secondary batteries of Examples 1, 2, and 4, and Comparative Example 1, which were pouch cells.
[0095] [Comparative Example 2] A lithium secondary battery of Comparative Example 2 was obtained in the same manner as in Example 1, except that a first coating layer was not laminated on the surface of the lithium metal plate, and a saturated solution obtained by adding about 0.5 mass % of LiDFP to the nonaqueous electrolyte was used as the nonaqueous electrolyte.
[0096] [Comparative Example 3 and Comparative Example 5] Lithium secondary batteries of Comparative Examples 3 and 5 were obtained in the same manner as in Example 1, except that the first coating layer was not laminated on the surface of the lithium metal plate.
[0097] [Example 3] A lithium secondary battery of Example 3 was obtained in the same manner as in Example 1, except that a second coating layer containing gold as a main component was formed on the surface of the lithium metal plate, and then a first coating layer was laminated on the surface of the second coating layer in the same manner as in Example 1. The second coating layer was formed according to the following procedure.
[0098] (Formation of second coating layer) A second coating layer was formed on the surface of the lithium metal plate using the sputtering method in the following procedure. A JEOL MAGNETRON SPUTTERING DEVICE (JUC-5000) was used as the sputtering device, and gold with a purity of 99.99% was used as the target. Gold was sputtered onto the surface of the lithium metal plate with a height of 25 mm from the surface of the lithium metal plate to the target and a coating current of 10 mA. Sputtering was performed for 5 minutes each time, a total of three times. All of the above operations were performed in a dry room. The coating amount of the second coating layer was approximately 0.25 mg / cm. 2 It was.
[0099] [Comparative Example 4] A lithium secondary battery of Comparative Example 4 was obtained in the same manner as in Example 3, except that the first coating layer was not laminated on the surface of the lithium metal plate.
[0100] (Initial charge / discharge) Each of the obtained lithium secondary batteries was subjected to two cycles of initial charge and discharge at 25°C under the following conditions. Charging was performed by constant current constant voltage (CCCV) charging with a charging current of 0.1 C and a charging voltage of 4.7 V, and the charging termination condition was that the charging current was 0.05 C. Discharging was performed by constant current (CC) discharging with a discharging current of 0.1 C and a discharge termination voltage of 2.0 V. A rest period of 10 minutes was provided after each charging and discharging. Here, 1 C is the current value per unit area of the positive electrode of 6.0 mA / cm. 2 It was decided.
[0101] (XPS measurement) The negative electrodes after the initial charge and discharge according to the above-mentioned Example 1, Example 2, and Comparative Example 1 to Comparative Example 3 were subjected to XPS measurement according to the following procedure. Each lithium secondary battery in a fully discharged state after the initial charge and discharge was disassembled in an argon atmosphere with a dew point of -60°C or less, the negative electrodes were taken out, washed with dimethyl carbonate, and then dried under reduced pressure at room temperature. The obtained negative electrodes were sealed in a transfer vessel in an argon atmosphere, and XPS measurement was performed on the first coating layer surface of the negative electrodes in the above-mentioned Example 1, Example 2, and Comparative Example 1 under the above-mentioned conditions. In addition, XPS measurement was performed on the lithium metal plate surface in Comparative Example 2 and Comparative Example 3. From the obtained spectrum, the peak position of P2p was obtained by the above-mentioned method.
[0102] (Charge-discharge cycle test) The lithium secondary batteries of Examples 3 and 4, Comparative Examples 4 and 5 after the initial charge and discharge were subjected to 80 charge and discharge cycle tests at 25° C. under the following conditions. Charging was performed by constant current constant voltage (CCCV) charging with a charging current of 0.2 C and a charging voltage of 4.7 V, and the charging termination condition was until the charging current reached 0.05 C. Discharging was performed by constant current (CC) discharging with a discharging current of 0.1 C and a discharge termination voltage of 2.0 V. A rest period of 10 minutes was provided after each charging and discharging.
[0103] (Capacity retention rate after charge / discharge cycle test) The percentage of the discharge capacity at the 80th cycle to the discharge capacity at the 1st cycle in the charge-discharge cycle test was defined as the "capacity maintenance rate (%) after charge-discharge cycles."
[0104] (Number of cycles until short circuit occurs) The number of cycles until a short circuit occurred in Examples 1 to 4 and Comparative Examples 1 to 5 was evaluated by the following procedure. After the above initial charge and discharge, a charge and discharge cycle test was performed in the same manner as in the above charge and discharge cycle test, without setting an upper limit on the number of cycles. The occurrence of a short circuit was confirmed by the presence or absence of a decrease in Coulomb efficiency due to an increase in the amount of charged electricity during the charge and discharge cycle. Specifically, it was determined that a short circuit occurred when the amount of charged electricity increased compared to the immediately preceding cycle and the Coulomb efficiency fell below 99%. The above "Coulomb efficiency" is the percentage of the discharge capacity relative to the amount of charged electricity in that cycle.
[0105] Table 1 shows the P2p peak positions and the number of cycles until short circuit occurrence obtained by XPS measurement in Example 1, Example 2, and Comparative Examples 1 to 3. Table 2 shows the number of cycles until short circuit occurrence and the capacity retention rate after charge / discharge cycles in Example 3, Example 4, Comparative Example 4, and Comparative Example 5.
[0106] [Table 1]
[0107] [Table 2]
[0108] As shown in Table 1, the X-ray photoelectron spectroscopy spectrum of the surface of the first coating layer shows that P 2P In Examples 1 and 2, the peak position of the above P 2P In comparison with Comparative Example 1 to Comparative Example 3, in which the peak position of the peak position is less than 135 eV, the number of cycles until the occurrence of a short circuit was large, and the occurrence of a short circuit was suppressed. In addition, from the result of Comparative Example 2, it can be seen that the occurrence of a short circuit was further suppressed in Examples 1 and 2, even compared with the case where LiDFP was added as an electrolyte additive. Note that, in Examples 1 and 2, the coating amount of LiDFP in the first coating layer was about 0.06 mg / cm.2 Comparative Example 1 and Comparative Example 2 2P The peak positions are different from each other, which is presumably because in Comparative Example 1, LiDFP was decomposed during the initial charge / discharge and the first coating layer disappeared.
[0109] As shown in Table 2, Example 4, which had only the first coating layer, suppressed the occurrence of short circuits more than Comparative Example 4, which had only the second coating layer, and Comparative Example 5, which had no coating layer. Moreover, Example 3, which had the first coating layer and the second coating layer, suppressed the occurrence of short circuits more significantly than Example 4, which had only the first coating layer, and Comparative Example 4, which had only the second coating layer, and it was shown that by providing the first coating layer and the second coating layer, a synergistic effect can be obtained in suppressing short circuits.
[0110] The above results demonstrate that the negative electrode for a lithium secondary battery can suppress the occurrence of short circuits in the lithium secondary battery. [Industrial Applicability]
[0111] The present invention can be applied to lithium secondary batteries used as power sources for personal computers, flying objects such as airplanes, electronic devices such as communication terminals, automobiles, and the like. [Explanation of symbols]
[0112] 1. Lithium secondary battery 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device
Claims
1. A negative electrode substrate layer; A first coating layer that is laminated on the negative electrode base material layer and is located on the outermost surface; a lithium metal layer laminated between the negative electrode substrate layer and the first coating layer; Equipped with the first coating layer contains a phosphorus compound containing a fluorine atom and an oxygen atom, In the spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy, 2P The negative electrode for a lithium secondary battery has a peak position of 135 eV or more.
2. A negative electrode substrate layer, A first coating layer that is laminated on the negative electrode base material layer and is located on the outermost surface; a deposition-type lithium metal layer that dissolves during discharge and deposits between the negative electrode substrate layer and the first coating layer during charge; Equipped with the first coating layer contains a phosphorus compound containing a fluorine atom and an oxygen atom, A negative electrode for a lithium secondary battery, wherein a P 2P peak position in a spectrum measured by X-ray photoelectron spectroscopy on the surface of the first coating layer is 135 eV or higher.
3. a second coating layer is provided between the negative electrode base material layer and the first coating layer and is laminated directly or indirectly on a surface of the negative electrode base material layer; 3. The negative electrode according to claim 1, wherein the second coating layer is mainly composed of at least one of gold, tin, zinc, magnesium, aluminum, platinum, a lithium alloy containing any of these metals, and carbon nanotubes.
4. A negative electrode as described in claim 3, wherein the lithium metal layer or the precipitated lithium metal layer is laminated or precipitated between the negative electrode substrate layer and the second coating layer, between the first coating layer and the second coating layer, or a combination thereof.
5. A lithium secondary battery comprising the negative electrode according to any one of claims 1 to 4.
6. A lithium metal layer is laminated directly or indirectly on the surface of a negative electrode substrate layer; and coating a first coating layer-forming material containing a phosphorus compound containing fluorine atoms and oxygen atoms on the negative electrode base material layer to form a first coating layer on the negative electrode base material layer so as to be located on the outermost surface of the negative electrode base material; In the spectrum of the surface of the first coating layer by X-ray photoelectron spectroscopy, 2P The method for producing a negative electrode for a lithium secondary battery, in which the peak position is 135 eV or more.
7. A method for producing a lithium secondary battery, comprising: producing a lithium secondary battery by using the negative electrode according to any one of claims 1 to 4 or the negative electrode obtained by the method for producing a negative electrode according to claim 6.
Citation Information
Patent Citations
Negative electrode material and manufacture thereof, and nonaqueous electrolyte battery using it
JP1993074457A
Active material for nonaqueous electrolyte battery, and nonaqueous electrolyte battery
JP2011124154A
Secondary battery, and method for manufacturing the same
JP2012238461A
Power storage device and electronic device
JP2018092928A
Negative electrode including multiple protective layers and lithium secondary battery including the same
JP2019509606A
